Usability of voice and picture records violating personal rights in application of law by German courts (Academic Journal of Internal Affairs, 2018)
Due to technical development everyone has opportunities to make records by own cellular phone, the majority of people has internet connection, desktops and laptops became indispensable part of everyday life and recording equipment - Dictaphones, video cameras- are available with multifunctionality for anybody. There are no technical obstacles of copying and making records public. In road traffic are video cameras more and more prevalent. Making voice, picture or video records secretly might have no special reasons, but also for use as evidence even if in time of making the exact way of application was not cleared yet. In the course of production and application of records personal rights of others can be hurt, which will unavoidably bring along a clash of interests to be released by the authorities. The latter ones should answer the question if safeguarding of interests of the record maker or the interest of the recorded person on secrecy has priority or there are other aspects to be considered, too. This paper intends to present briefly how interests are balanced and how decisions on applicability of records are made in Germany. Due to the author’s profession the way of access is first of all from the aspects of a criminal judge.
Keywords: under rights; records; Germany